Effectiveness Of Using Rice Husk As A Bioadsorbent On Amonia (NH3) And Nitrite (NO2-) Levels In Liquid Waste Of The Tofu Industry - Saputri, Dea Dwi; Jusuf, Herlina; Maksum, Tri Septian (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Tofu industry liquid waste contains ammonia (NH3) and nitrite (NO2-) compounds which can cause pollution if released into the environment without prior processing. Rice husks can be used to make active carbon which acts as a bioadsorbent against various contaminants which is cheap and easy to obtain. The research aims to test the effectiveness of using rice husks in doses of 5 grams, 10 grams and 15 grams as a bioadsorbent on NH3 and NO2- levels in liquid waste at the Rina Tofu Factory. This type of quasi-experimental research with a Completely Randomized Design (CRD) approach. Determination of NH3 and NO2- levels using the spectrophotometric method with three replications. Data were analyzed using the One-Way ANOVA test (? = 5%). The research results showed that the initial concentration of NH3 was 0.16 mg/L and fluctuated after contact with rice husks (5 gram dose: RI = 0.13 mg/L, RII = 0.15 mg/L, RIII = 0.25 mg/L; 10 gram dose: RI = 0.21 mg/L, RII = 0.27 mg/L, RIII = 0.12 mg/L dose 15 grams: RI = 0.32 mg/L, RII = 0.26 mg/L, RIII = 0.30 mg/L). Meanwhile, the initial concentration of NO2- was 0.043 mg/L and increased after contact with rice husks (5 gram dose: RI = 0.091mg/L, RII = 0.138 mg/L, RIII = 0.125 mg/L; 10 gram dose: RI = 0.117 mg/L, RII = 0.151 mg/L, RIII = 0.122 mg/L; 15 gram dose: RI = 0.112 mg/L, RII = 0.137 mg/L, RIII = 0.126 mg/L). There is no difference in the effectiveness of using rice husks on NH3 (?-value = 0.114) and NO2- (?-value = 0.750) levels in liquid waste from the tofu industry. Further research needs to be carried out regarding variations in contact time between rice husks and liquid waste from the tofu industry.